2000
DOI: 10.1016/s0735-1097(00)00962-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, interpretation and clinical potential of QT dispersion

Abstract: QT dispersion was originally proposed to measure spatial dispersion of ventricular recovery times. Later, it was shown that QT dispersion does not directly reflect the dispersion of recovery times and that it results mainly from variations in the T loop morphology and the error of QT measurement. The reliability of both automatic and manual measurement of QT dispersion is low and significantly lower than that of the QT interval. The measurement error is of the order of the differences between different patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
458
9
15

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 543 publications
(505 citation statements)
references
References 142 publications
23
458
9
15
Order By: Relevance
“…If the increased QT interval dispersion in the subgroup of hypertensives with the concentric hypertrophy geometric pattern is related to a greater susceptibility to serious ventricular arrhythmias, then it could explain the greater cardiovascular mortality associated with this left ventricular geometry, 25 although this point remains controverse. 40 QT interval dispersion is no longer believed to represent spatial inhomogeneity of repolarization throughout the ventricular myocardium, 13 as originally proposed. 1 Several recent studies 41,42 have demonstrated that it probably indicates a global ventricular repolarization abnormality, reflected by an altered, more complex, spatial vectorcardiographic T-wave loop, as would be expected to occur in the hypertrophied myocardium with increased interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the increased QT interval dispersion in the subgroup of hypertensives with the concentric hypertrophy geometric pattern is related to a greater susceptibility to serious ventricular arrhythmias, then it could explain the greater cardiovascular mortality associated with this left ventricular geometry, 25 although this point remains controverse. 40 QT interval dispersion is no longer believed to represent spatial inhomogeneity of repolarization throughout the ventricular myocardium, 13 as originally proposed. 1 Several recent studies 41,42 have demonstrated that it probably indicates a global ventricular repolarization abnormality, reflected by an altered, more complex, spatial vectorcardiographic T-wave loop, as would be expected to occur in the hypertrophied myocardium with increased interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is that, as our patients were all type 2 diabetics as well, possibly our results could not be applied to the general population of hypertensives without diabetes mellitus. Finally, the well-recognized poor reproducibility and lack of standardization, particularly important in QT interval dispersion measurements, 13 do not need to be overemphasized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTc dispersion was defined as the difference between the minimum and maximum heart rate-adjusted QT interval among the 12 EKG leads. QTc dispersion was considered abnormal if it was longer than 50 msec (19).…”
Section: Methodsmentioning
confidence: 99%
“…Thus the slope of the linear relationship between the log-transformed QT and RR 100 defined the exponent to which the RR interval ratio should be raised to QTc. As a second method, we used an automated threshold approach so that we could compute an hourly average for the QT interval over several days (3,13,15,22). Briefly, the ECG traces recorded for each hour were aligned to the peak of R wave to generate an average trace, the Q point was defined as the base of the QRS complex (where the slope of the profile changed from negative to positive), and the T point was defined to where the ECG returned 75% of the way from the minima of the T wave to the isoelectric level.…”
Section: Ecg Telemetrymentioning
confidence: 99%